Annual Report on the Working of State Electricity Boards and Electricity Department November, 1997 - Planning Commission (Planning Commission, 1997)
This report, brought out every-year by Power and Energy Division of the Planning Commission, is the Tenth in the series that updates and analyses the data on the working of the State Electricity Boards in the country. Most of the data contained in this document has been obtained from the State Electricity Boards (SEBs) and Electricity Departments (EDs) of the States/UTs in connection with the discussions held in the Planning Commission to estimate the financial resources for the Annual Plan 1997-98. A brief analysis covers the performance of the power utilities during 1992-93, 1993-94, 1994-95, 1995- 96, the latest estimates for 1996-97 and the Annual Plan projections for 1997-98. Information for the earlier years is also provided in respect of a few important parameters. Information pertaining to Central sector and private sector power utilities has been collected from Ministry of Power, Central Electricity Authority and published reports/documents etc.
(Power and Energy Division) Planning Commission Govt. of India
(Power and Energy Division) Planning Commission Govt. of India